2006
DOI: 10.1007/s00415-006-0203-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis in Jordan: a clinical and epidemiological study

Abstract: Jordan is a medium-high risk country for MS, with prevalence higher than what has previously been reported, possibly representing an increase in incidence. Clinical and demographic characteristics are similar to most reports worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
71
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 18 publications
(18 reference statements)
13
71
3
Order By: Relevance
“…Further features found among Isfahan MS patients include: (1) increasing female preponderance over the recent decade [23]; (2) highest rates among the 30- to 39-year age group, decreasing with increasing age; (3) high percentage in early-onset MS, and (4) the lower frequency of oligoclonal IgG bands in CSF of Isfahan MS patients than in the West [14]. Similar reports from Japan and Jordan may be evidence that oligoclonal IgG bands are less frequent in the CSF of Asian MS patients than MS patients in the West; however, more accurate studies are required to support this hypothesis [14,24,25]. …”
Section: Discussionmentioning
confidence: 60%
“…Further features found among Isfahan MS patients include: (1) increasing female preponderance over the recent decade [23]; (2) highest rates among the 30- to 39-year age group, decreasing with increasing age; (3) high percentage in early-onset MS, and (4) the lower frequency of oligoclonal IgG bands in CSF of Isfahan MS patients than in the West [14]. Similar reports from Japan and Jordan may be evidence that oligoclonal IgG bands are less frequent in the CSF of Asian MS patients than MS patients in the West; however, more accurate studies are required to support this hypothesis [14,24,25]. …”
Section: Discussionmentioning
confidence: 60%
“…17 ON is less frequent in South America and in the Mediterranean region but newer studies have reported an increasing prevalence in the last few decades. [18][19][20] Some studies have shown that individuals who migrate before puberty have the incidence of MS in the area to which they have migrated. [20][21][22] This suggests a possible interaction between the ethnic origin of the patient, the latitude, and whatever is the factor (or factors) that triggers MS. Other studies have suggested that less sun exposure at increasing latitude might be a risk factor for MS, 23,24 and vitamin D deficiency is an additional potential explanation for some of the epidemiological differences in MS. 25,26 In addition, an increased incidence of ON during the spring season has been reported.…”
Section: Epidemiologymentioning
confidence: 99%
“…Two studies were found on the prevalence of MS in Jordan [12,26] . The first was conducted between 1992 and 1993 at the Jordan University Hospital and the King Hussain Medical Center in Amman, the capital of Jordan.…”
Section: Jordanmentioning
confidence: 99%